KORELASI DAN IMPLIKASI MEMPELAJARI HADIS NABI TERHADAP KETENANGAN HATI JAMAAH LANGGAR KIDUL AL-MUHAJIRIN SIDOARJO - Nurul Budi Murtini; Bisri Tujang; Irfan Yuhadi (Sekolah Tinggi Dirasat Islamiyah Imam Syafi'i Jember, 2023)
Among the basic knowledge that a Muslim needs to learn is the hadith of the Prophet Sallallaahu ‘alaihi wa Sallam. Hadith is everything that is based on the Prophet Sallallaahu ‘alaihi wa Sallam, whether in the form of; words, deeds, agreements and characteristics. The calm that can make the heart feel peaceful is when you feel at ease in receiving the news conveyed by His Messenger in the introduction of Asma’, His Attributes and perfections. This study aims to examine the correlation and implications of studying the Prophet’s hadith on sobriety. The approach used in this study is a quantitative approach. The population of this study is the Langgar Kidul Al-Muhajirin Sidoarjo congregation who participated in the study of the hadith of the Prophet sallallaahu 'alaihi wa Sallam. The number of samples is 30 people taken by simple random sampling technique. The instrument used is a questionnaire with a Likert scale. The data analysis technique used simple linear regression with the help of SPSS version 23. The results of this study indicate that there is a significant positive correlation between studying the Prophet’s hadith and sobriety in the Langgar Kidul Al-Muhajirin Sidoarjo congregation. With a strong relationship level. The magnitude of the implications of studying the Prophet’s hadith for sobriety in the Langgar Kidul Al-Muhajirin Sidoarjo Congregation is 49%.